Pengaruh Variabel Terpilih terhadap Kinerja Geuchik sebagai Pimpinan Gampong "Studi Kasus Kecamatan Blang Mangat Kota Lhokseumawe Provinsi Nanggroe Aceh Darussalam" - Aiyub Aiyub (Jurnal Aplikasi Manajemen, 2010)
The research have been done in district of Blong Mangat town of Lhokseumawe as a mean to knows is education, training, motivation, job experiences, loyal, and job culture factors can influences chief of village performance. Based on result of statistical analysis proves that the level of education (x1), training (x2), Motivation (x3), job experience (x4), loyal (x5) and job culture (x6) together has significant influences to chief of village performance in district of Blong Mangat. Tightly relation between variable (x1, x2, x3, x4, x5, x6) with independent variable (Y) proved by level of correlation coefficient value that is 0,924 or 92, 4. Giving of Motivation to subordinate especially chief of village by area leader is not always in physical or just material motivation, but have boosting ambition how to have good behavior good work, and gives high confidence to ability in finalizes duties all daily in instituting government of village.